Formulación de los subprocesos habilitantes de asesoría “Medición, Análisis y Mejora Continua-Seguimiento” para la gestión por resultados en la Universidad Nacional de Loja, año 2022 - Ordóñez Garrido, Johanna Katherine (2023)
This research report, called Formulation of the enabling sub-processes of "Measurement, Analysis and Continuous Improvement-Monitoring" for results-based management at Universidad Nacional de Loja, year 2022, was developed in order to identify, understand and reflect, the development of the tasks that are oriented to institutional quality assurance in both academic and administrative areas; thus proposing a manual proposal that shows the order of activities and facilitates the understanding of officials or users the completion and delivery of the procedures. The methodology used in the research had a qualitative approach due to the collection and analysis of the information obtained during the institutional documentary review, with the application of information techniques such as the observation sheet and the interview applied to the focus group on the object of study. With the support of the inductive, analytical and synthetic methods, it allowed in the first instance to recognize and identify the problems of the subprocesses through the situational diagnosis, to then analyze and break down into individual parts the inputs, activities, outputs and the roles of key actors, managing to synthesize the information in the proposals within a manual and flow charts; Finally, with the due socialization of the proposals to the members of the Coordination of Evaluation and Quality Assurance, previously fulfilling several stages of review, feedback and validation, for its subsequent delivery and implementation in the university, in order to maintain the efficiency and effectiveness of institutional quality management by offering services that are tailored to the needs of the university community.